THE EFFECT OF HEADSPROUT EARLY READING PROGRAM (HERP) ON STUDENTS READING COMPREHENSION WITH INTELLECTUAL DISABILITY (Pre-Experimental at SLB Negeri 5 Kota Bengkulu) - Endang Haryanto; Friska Dwi Fuji Lestari (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
This study aims to determine the differences in cognitive learning outcomes (in the form of pre-test and post-test scores) of students in class VII as experimental class at SLB Negeri 5 Kota Bengkulu, by providing treatment using the Headsprout Early Reading Program (HERP). This type of research is Pre-Experimental with Quantitative approach. The population is seventh grade students of SLB Negeri 5 Kota Bengkulu in the academic year 2020/2021 with 6 students were taken as samples. Research data were collected through Pre-test and Post-test and documentation. The results showed a significant change in the experimental class with an average value of post-test 76.1 while in the score pre-test an average value of 56.1. The post-test results show that the Headsprout Early Reading program can improve students' Reading Comprehension. Thus, the Headsprout Early Reading Program (HERP) can be one of effective program to increase students‟ reading comprehension specially with Intellectual Disability.